Answer:
<em>Answer: C. 32 cm</em>
Step-by-step explanation:
<u>Triangle Inequality Theorem
</u>
Let y and z be two of the side lengths of a triangle. The length of the third side x cannot be any number. It must satisfy all the following restrictions:
x + y > z
x + z > y
y + z > x
Combining the above inequalities, and provided y>z, the third size must satisfy:
y - z < x < y + z
We know the triangle has two congruent angles, which means the triangle is isosceles, i.e., it has two congruent sides.
We are given two side lengths of 16 cm and 32 cm. The third side must have a length of 16 cm or 32 cm for the triangle to be isosceles.
If the third side had a length of 16 cm then the lengths would be 16-16-32. But that combination cannot form a triangle because of the condition stated above.
If y=16, z=16, and x=32 (the worst possible combination), then the inequality
0 < x < 32
wouldn't be satisfied, thus the third side cannot have a length of 16 cm and it must have a length of 32 cm
Answer: C. 32 cm
Answer:
72 cups=4.5 gallons
72 cups=18 quarts
72 cups=36 pints
Step-by-step explanation:
To find out how many pints are in 72 cups you have to divide the volume value by 2. To find out how many quarts are in 72 cups you have to divide the volume value by 4. To find out how many gallons are in 72 cups you have to divide the volume value by 16.
Hope this helped for you!
A because 114 - 2 = 112.
112 + 114 = 226!
Answer: <u>105m²</u>
Formula for Area of Circle: A = π r²
so, A = 3.14 (6)² (I got 6 because radius is half the diameter)
Don't forget to divide the final area of the circle in half, because It's only a semicircle.
Formula for Triangle: A = ![\frac{bh}{2\\}](https://tex.z-dn.net/?f=%5Cfrac%7Bbh%7D%7B2%5C%5C%7D)
so, A =
(again, the "6" is just the diameter divided in half which forms the base of ONE triangle.)
You need to multiply the final area of the triangle by 2 since there are 2 triangles.
Step-by-step explanation:
Cos Milky said it. Trust Milky. Milky smart.
Answer is 17.
Both values are given where:
a = 7 and b = 3
Substitute the values into the given expression.
( 2 x 7 ) + 3
14 + 3 = 17
Hope it helps :]